Biochemical characterization and DNA repair pathway interactions of Mag1-mediated base excision repair in Schizosaccharomyces pombe. - Alseth, I; Osman, F; Korvald, H; Tsaneva, I; Whitby, M; Seeberg, E; Bjørås, M (2005)
The Schizosaccharomyces pombe mag1 gene encodes a DNA repair enzyme with sequence similarity to the AlkA family of DNA glycosylases, which are essential for the removal of cytotoxic alkylation products, the premutagenic deamination product hypoxanthine and certain cyclic ethenoadducts such as ethenoadenine. In this paper, we have purified the Mag1 protein and characterized its substrate specificity. It appears that the substrate range of Mag1 is limited to the major alkylation products, such as 3-mA, 3-mG and 7-mG, whereas no significant activity was found towards deamination products, ethenoadducts or oxidation products. The efficiency of 3-mA and 3-mG removal was 5-10 times slower for Mag1 than for Escherichia coli AlkA whereas the rate of 7-mG removal was similar to the two enzymes. The relatively low efficiency for the removal of cytotoxic 3-methylpurines is consistent with the moderate sensitivity of the mag1 mutant to methylating agents. Furthermore, we studied the initial steps of Mag1-dependent base excision repair (BER) and genetic interactions with other repair pathways by mutant analysis. The double mutants mag1 nth1, mag1 apn2 and mag1 rad2 displayed increased resistance to methyl methanesulfonate (MMS) compared with the single mutants nth1, apn2 and rad2, respectively, indicating that Mag1 initiates both short-patch (Nth1-dependent) and long-patch (Rad2-dependent) BER of MMS-induced damage. Spontaneous intrachromosomal recombination frequencies increased 3-fold in the mag1 mutant suggesting that Mag1 and recombinational repair (RR) are both involved in repair of alkylated bases. Finally, we show that the deletion of mag1 in the background of rad16, nth1 and rad2 single mutants reduced the total recombination frequencies of all three double mutants, indicating that abasic sites formed as a result of Mag1 removal of spontaneous base lesions are substrates for nucleotide excision repair, long- and short-patch BER and RR.